Le design comme vecteur de changement social, les initiatives de Julien Hébert au Québec dans les années 1960 et 1970 - Racine, Martin (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 2015)
This article examines a lesser-known dimension of the career and work of Julien Hébert, one of the most influential figures in Quebec and Canadian design from the 1950s to the 1980s. By revisiting Hébert’s archives, it sheds light on significant initiatives he developed in order to use design as a tool for cultural and social change. These are a project for a Montreal-based Institute of Design and another that aimed at tackling unemployment through design practice. These exemplify Hébert’s understanding of design as a discipline that offers more than the creation of beautiful products and functional furniture. For him, it was a means to change society and to improve the wellbeing of its citizens.